COMPARATIVE ANALYSIS OF PSYCHOLOGICAL FACTORS OF THE MANIFESTATION OF AGGRESSION IN SPORT - Stepanyan, A. G. (Modern Psychology, 2020)
The article attempts to study the individual characteristics of sports students and non-sports students through research, identify the effects and interactions of interactions in sports and the relationship between behavior in the process of psychological training of athletes. An attempt has also been made to study those individuals for whom the aggressive behavior model may be used more often. Research has shown that doing sport and specific types of sport may have some effects on the aggression of athletes. But it is possible to have the opposite version too. It means that doing sport and specific types of sport may help reduce the level of aggression. Analysis of theoretical approaches to defining the concept of aggression allows to conclude that every scientific direction in psychology has a unique definition and of the given event his approach to the study of phenomenology.